Does Equity Investment Decision Differ among Demographic Characteristics of the Investors? - Mohan Prasad Sapkota; Dilli Raj Sharma; Jeetendra Dangol (Management Dynamics, 2024)
This study aims to examine the differences in equity investment decisions among demographic characteristics of the respondents. This study is based on a quantitative research approach with a descriptive cum analytical research design. This study utilizes a purposive sampling technique. The total sample size from management faculty, chartered accountants, and staff from investment companies of this study is 770. However, final usable responses are 497, representing a 64.55 percent response rate. This study utilizes descriptive statistics, an independent sample t-test, and an ANOVA test. This study found that investment decisions between males and females are significantly different. Similarly, investment decisions of divorced investors are significantly different from those of single, married, and other investors. However, investment decisions do not significantly differ from academic qualifications and the profession of the respondents. Finally, this study reveals that investment decisions are different among different demographic characteristics, especially gender and marital status of the investors. Hence, this study concluded that investors’ financial decisions are shaped by their personal, social, and academic backgrounds.